UNDERSTANDING PEOPLE’S PERCEPTIONS OF TESLA - Putri, Elin Eprilin Fitrian Miela; Susilastuti, Dewi H. (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
This research presents society's perceptions of Tesla through comments from the videos on their official YouTube channel. This research is focused on the perceptions of society through comments sections from four different videos. This research uses Poststructuralism as an approach that is supported by deconstruction theory by Derrida. From the deconstruction theory, this research employs the concept of difference to find out about many perceptions of Tesla in society. This research applies a qualitative descriptive technique, in which the author reports and analyses existing data. The data is taken from the comment section of four different videos from Tesla’s YouTube channel. From analyzing the data relating to the theory, it is found that Tesla has several perceptions in society which are that Tesla is a high-tech innovation, Tesla is environmentally friendly, Tesla is expensive, Tesla is high-maintainable, and Tesla is a family car. These new perspectives show that the car has been accepted into society and plays a significant role in society.